Interspecific and intraspecific cross-compatibility of Durio kutejensis and hybrid Durio zibethinus x kutejensis - Rudarmono Rudarmono; NOER RAHMI ARDIARINI; BUDI WALUYO; SUMERU ASHARI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rudarmono, Ardiarini NR, Waluyo B, Ashari S. 2022. Interspecific and Intraspecific cross-compatibility of Durio kutejensis and hybrid Durio zibethinus x kutejensis. Biodiversitas 23: 1837-1843. Lai (Durio kutejensis) and Mandong (Durio zibethinus x kutejensis) fruits that have advantages and high consumer preference values. Fruit productivity and development of Lai and Mandong plant varieties are still not optimal. The aim of this study was to analyze the level of incompatibility of interspecific and intraspecific crosses between Lai (D. kutejensis) and Mandong (D. zibethinus x kutejensis hybrid) plants. Artificial crosses were made utilizing flower samples from Mahakam, Kutai, and Batuah types of Lai plants, as well as Mandong varieties of Mandong, employing a scheme of 20 crossings that included a combination of these varieties (12 treatments), as well as each variety from the same flower and tree (8 treatments). The intensity level and incompatibility classification were determined according to Wang's (1963) method, which was based on the number of fruits formed from artificial crosses, and the pollen incompatibility intensity level (IIL) was determined according to the ratio of flowers that produced fruit from the cross to the total number of flowers crossed. The results showed that overall crosses of the same flower (selfing) from three varieties of Lai and one variety of Mandong were incompatible. Lai Mahakam x Lai Batuah crosses yielded 14.28 % harvested fruit, Lai Mahakam x Lai Mahakam crosses yielded 18.75 % harvested fruit, Lai Kutai x Lai Kutai crossings yielded 14.81 % harvested fruit, while a cross of Durian Mandong x Lai Batuah yielded 16.67 % harvested fruit. It shows partially compatible. The complete compatibility value showed the number of harvested fruit ranged from 23.44 to 46.77%, with the most significant being obtained from a Lai Mahakam x Durian Mandong cross. The Mahakam, Kutai, Batuah, and Mandong varieties are compatible with all pollen sources.